The Ubiquitin E3/E4 Ligase UBE4A Adjusts Protein Ubiquitylation and Accumulation at Sites of DNA Damage, Facilitating Double-Strand Break Repair - Baranes-Bachar, K; Levy-Barda, A; Oehler, J; Reid, D; Soria-Bretones, I; Voss, T; Chung, D; Park, Y; Liu, C; Yoon, J; Li, W; Dellaire, G; et al. (Cell Press, 2018)
Double-strand breaks (DSBs) are critical DNA lesions that robustly activate the elaborate DNA damage response (DDR) network. We identified a critical player in DDR fine-tuning: the E3/E4 ubiquitin ligase UBE4A. UBE4A's recruitment to sites of DNA damage is dependent on primary E3 ligases in the DDR and promotes enhancement and sustainment of K48- and K63-linked ubiquitin chains at these sites. This step is required for timely recruitment of the RAP80 and BRCA1 proteins and proper organization of RAP80- and BRCA1-associated protein complexes at DSB sites. This pathway is essential for optimal end resection at DSBs, and its abrogation leads to upregulation of the highly mutagenic alternative end-joining repair at the expense of error-free homologous recombination repair. Our data uncover a critical regulatory level in the DSB response and underscore the importance of fine-tuning the complex DDR network for accurate and balanced execution of DSB repair.